Tourism coopetition: An introduction to the subject and a research agenda - Chim-Miki, Adriana F.; Batista-Canino, Rosa M. (International business review, 2017)
•Introduce a definition of Tourism Coopetition.•Verify the current status of research on coopetition applied to tourism.•Show coopetition as a behavior representing the organizational form of tourism destinations, based on interdependence.•Present a research agenda, in order to lead coopetition as a behavioral approach of tourism actors in the destination. This paper aims to verify the current status of the research on coopetition applied to Tourism. In order to overcome the lack of tools for analyzing competitive advantage generated by relational components, this paper suggests the use of the coopetition construct as a methodological tool for analyzing the cooperation in networks for the management of tourism destinations. To that end, we performed a bibliometric analysis on ‘tourism coopetition' in scientific research papers published from 1995 to 2015 and indexed in the Web of Science and SciVerse Scopus databases. This helped us to conclude that coopetition is a behavior representing the key organizational methods of tourism destinations, especially when considering the interdependence and complementarity of this sector; thus, it should be a fundamental topic of tourism research. In this sense, the paper presents a research agenda in order to establish coopetition as key to understanding the behavior of all those involved in tourism at a particular destination.